”Jag tror på något”: Konstruktioner av tro och tilltro (Sociologisk Forskning, 2013)
”I believe in something”: Constructions of Beliefs in SwedenResearch results are dependent on how social phenomena are conceptualized. In the present article, consequences are discussed of the standardized conceptualization of religiosity as ”church-oriented”. In its place, a multifaceted approach to the phenomenon of religious belief is suggested. This approach was used for an analysis on how eleven Swedish women and men with different religious and spiritual as well as non-religious and atheist affiliation talk about beliefs. The results suggest that beliefs were meaningful because they related to specific perceptions of a Zeitgeist. It was hereafter underlined that belief in ”something” or other brief descriptions of the sacred placed the sacred outside of the individual. Finally, while subjective authority is valued for choosing to believe, this subjectivity seems in part to be dependent on collective dimensions of recognition. The value of choosing beliefs can be conceptualized as a meaningful yet analytically distinct aspect of belief co-existing with descriptions of the sacred. Thus, it is concluded that a multifaceted approach to religious belief may develop our understanding of religion and religiosity in contemporary society